2016
DOI: 10.1007/s00380-016-0939-2
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal atrial fibrillation during intracoronary acetylcholine provocation test

Abstract: Intracoronary acetylcholine (ACh) provocation test is useful to diagnose vasospastic angina. However, paroxysmal atrial fibrillation (AF) often occurs during intracoronary ACh provocation test, leading to disabling symptoms. The aim of this study was to investigate the incidence and predictors of paroxysmal AF during the test. A total of 377 patients without persistent AF who underwent intracoronary ACh provocation test were included. Paroxysmal AF during ACh provocation test was defined as documented AF on el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Thus, it is safe to conclude that the SPT can be performed from either the LCA or RCA. Saito et al reported that Af is more likely to occur when the SPT is started from the RCA [29]. In this study, Af also occurred more frequently during RCA provocation in the group wherein the SPT was initiated from the RCA.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Thus, it is safe to conclude that the SPT can be performed from either the LCA or RCA. Saito et al reported that Af is more likely to occur when the SPT is started from the RCA [29]. In this study, Af also occurred more frequently during RCA provocation in the group wherein the SPT was initiated from the RCA.…”
Section: Discussionsupporting
confidence: 48%
“…Carefully performing SPT is necessary in the future. The rate of paroxysmal Af has been reported to be 8-17% [28,29], which may be influenced by whether the LCA or RCA is being provocative and by what provocation dose is being applied. Our data may have a higher frequency of Af; however, they do not seem to deviate from the conventional direction.…”
Section: Discussionmentioning
confidence: 99%
“…We advocate proceeding without transvenous pacing and applying caution with testing the right coronary or left-dominant circulations. Self-limiting atrial fibrillation is also common (8%), particularly during evaluation of right coronary vascular function ( 90 ). Patients undergoing clinically indicated coronary angiography typically have risk factors for cardiovascular disease, including atrial fibrillation.…”
Section: How To Assess Coronary Vascular Dysfunction In the Catheterimentioning
confidence: 99%
“…[15] During the ACh test, paroxysmal atrial fibrillation (PAF) is frequently (8.0-22.8%) provoked, is usually transient, and sometimes requires treatment with antiarrhythmic drugs or electrical cardioversion. [610] Although PAF during the ACh test is generally recognized as a minor complication, it may have clinical implications.…”
Section: Introductionmentioning
confidence: 99%